A cerium oxide-based material for fuel cells or electrolytic cells
By preparing NiO-loaded rare earth metal-doped ceria-based material with a rod-buckle one-dimensional structure, the problem of insufficient performance of high ionic conductivity electrode materials in the prior art is solved, and electrochemical performance with high current density and long-term stability in SOFC and SOEC is achieved.
Patent Information
- Application Number
- CN202410808293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-06-21
AI Technical Summary
In the prior art, how to develop high ionic conductivity ceria-based materials through different composite forms and/or doping techniques to obtain better performance electrode materials, especially in solid oxide fuel cells (SOFCs) and electrolytic cells (SOECs).
A ceria-based material is provided, and its general formula is NiO/Ce0.5M0.5O1.95. M represents the metal element La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc or Y. Through a specific preparation method, it includes dissolving 1,3,5-benzenetriacetic acid in ethanol-deionized aqueous solution, mixing the ceria-based material with a rare earth metal salt, heating and stir precipitation, washing, drying, and calcining at 500-900°C to obtain a ceria-based material with a rod-buckle one-dimensional structure.
The ceria-based material has a rod-beam structure with a high aspect ratio, which improves the ion conduction rate, forms a large three-phase boundary region and a well-connected network, provides sufficient active sites to facilitate gas adsorption and diffusion, significantly improves electrochemical performance, especially in SOFC and SOEC modes, which exhibit high current density and long-term stability.
Smart Images

Figure CN118841581B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cerium oxide-based material for a fuel cell or an electrolytic cell, belonging to the technical field of materials. Background Art
[0002] Solid oxide electrolysis cell (SOEC) is a highly efficient energy conversion device that can utilize renewable electricity from solar, wind, hydro or geothermal energy to electrolyze or co-electrolyze H2O and CO2 at higher temperatures (600-1000°C) to efficiently and economically produce synthesis gas. Its principle is the reverse process of solid oxide fuel cell (SOFC). This renewable energy cycle not only helps to reduce annual greenhouse gas emissions, but also promotes the large-scale grid connection of intermittent renewable energy, and is an effective way to achieve the strategic goal of "carbon neutrality". At present, the key to the research and development of efficient SOFC / SOEC is to design stable and efficient electrode materials and microstructures to achieve efficient mass transfer at the electrode three-phase interface.
[0003] In the prior art, cerium oxide (CeO2) is an important electrode or electrolyte material, especially rare earth-doped cerium oxide in solid oxide fuel cells (SOFCs), whose high oxygen ion conductivity makes it an ideal electrode material.
[0004] Rare earth-doped materials based on cerium oxide, as well as composite materials of cerium oxide and other metal oxides, how to further develop cerium oxide-based materials with high ionic conductivity through different composite forms and / or doping techniques to obtain electrode materials with better performance is an urgent problem to be solved by technicians in this field. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a cerium oxide-based material, wherein:
[0006] The cerium oxide-based material has NiO / Ce a M b O 1.95 The general formula of
[0007] In the general formula of the cerium oxide-based material, the M element represents a metal element La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc or Y;
[0008] The value of a is 0.5 to 0.9, the value of b is 0.1 to 0.5, and the sum of a and b is 1;
[0009] In the general formula of the cerium oxide-based material, "NiO" and "Cea M b O 1.95 "The molar ratio is x:y, and the value of x:y is 1:2 to 3:1;
[0010] The cerium oxide-based material has a one-dimensional rod bundle structure at the micrometer level;
[0011] The cerium oxide-based material is obtained by a preparation method comprising the following steps;
[0012] Step 1): 1,3,5-benzenetricarboxylic acid is dissolved in an ethanol-deionized water solution;
[0013] Step 2): mixing a cerium metal salt and a rare earth metal salt in a first molar ratio and dissolving them in deionized water;
[0014] The cerium metal salt is CeCl3, and the rare earth metal salt has the general formula of MCl3; or,
[0015] The cerium metal salt is Ce(NO3)3·6H2O, and the rare earth metal salt has a general formula of M(NO3)3·6H2O;
[0016] Furthermore, the M element in the general formula of the rare earth metal salt is the M element in the general formula of the cerium oxide-based material;
[0017] The first molar ratio is the ratio of a to b;
[0018] Step 3): Mix the solutions obtained in step 1) and step 2), heat to 50-100° C., and stir continuously until the precipitate no longer increases; wash and dry the precipitate obtained by centrifugation to obtain a rare earth metal-doped Ce-MOF material;
[0019] Step 4): dissolving Ni(NO3)2·6H2O and the rare earth metal-doped Ce-MOF material in an ethanol-deionized water solution in a second molar ratio, heating to 50-100° C., and continuously stirring until the precipitate no longer increases; washing and drying the precipitate obtained by centrifugation;
[0020] The second molar ratio is the value of x:y;
[0021] Step 5): The dried powder obtained in step 4) is calcined at a temperature of 500-900° C. to remove organic matter, thereby obtaining the cerium oxide-based material.
[0022] In a preferred embodiment of the present application, in step 1) and step 4), the ethanol-deionized water solution is a solution in which ethanol and deionized water are mixed in a volume ratio of 1:0.8 to 0.8:1; preferably, ethanol and deionized water are mixed in a volume ratio of 1:1.
[0023] In a preferred embodiment of the present application, in step 1), 1,3,5-benzenetricarboxylic acid is dissolved in the ethanol-deionized water solution, and the molar percentage after mixing is 0.3-0.8 mol / L.
[0024] In a preferred embodiment of the present application, in step 3), the solutions obtained in step 1) and step 2) are mixed, and the total metal ion concentration of Ce element and M element after mixing is 0.07-0.13 mol / L.
[0025] In a preferred embodiment of the present application, in the general formula of the cerium oxide-based material, M represents metal Gd. In another preferred embodiment of the present application, preferably, the first molar ratio is 9:1; preferably, the second molar ratio is 3:1, 2:1, 1:1 or 1:2; more preferably, the second molar ratio is 1:1.
[0026] In a preferred embodiment of the present application, the aspect ratio of the cerium oxide-based material is 4:1 to 12.5:1, and its diameter is 0.37 to 0.73 μm; preferably, the aspect ratio of the cerium oxide-based material is 4.3 to 5.8, and its diameter is 0.61 to 0.73 μm; preferably, the aspect ratio of the cerium oxide-based material is 5.8 to 7.2, and its diameter is 0.54 to 0.61 μm; preferably, the aspect ratio of the cerium oxide-based material is 7.2 to 9.6, and its diameter is 0.42 to 0.54 μm; preferably, the aspect ratio of the cerium oxide-based material is 9.6 to 12.1, and its diameter is 0.37 to 0.42 μm.
[0027] In a preferred embodiment of the present application, in step 3), the heating temperature is 60° C. Preferably, in step 3), the drying temperature is 70° C.;
[0028] Preferably, in step 4), the heating temperature is 60°C;
[0029] Preferably, in step 4), the drying temperature is 70°C;
[0030] Preferably, in step 5), the calcination temperature is 850° C.; preferably, the dried powder obtained in step 4) is placed in a muffle furnace for calcination.
[0031] Another aspect of the present invention provides an electrode material, wherein the electrode material comprises the above-mentioned cerium oxide-based material; the electrode material is an anode material or a cathode material; preferably, the electrode material is a cathode material.
[0032] Another aspect of the present invention provides a fuel cell, wherein the fuel cell adopts the above-mentioned electrode material.
[0033] In another aspect, the present invention provides an electrolytic cell, wherein the electrolytic cell adopts the above-mentioned electrode material.
[0034] The cerium oxide-based material for a fuel cell or an electrolytic cell of the present invention is a NiO-loaded rare earth metal-doped cerium oxide-based material having a rod-bundle-shaped one-dimensional structure obtained by a specific preparation method. The cerium oxide-based material of the present invention has a high aspect ratio due to its special one-dimensional rod-bundle-shaped structure, a short ion path for radial diffusion, and a fast ion conduction rate for axial transmission. In addition, the cerium oxide-based material of the present invention helps to form a self-sufficient or aligned structure, and can usually form a large three-phase boundary (TPB) area and a well-connected network in the electrode material, which can provide sufficient active sites to facilitate gas adsorption and diffusion, as well as rapid ion transport.
[0035] In terms of electrochemical performance, the cerium oxide-based material of the present invention can be used as an electrode material, in particular, as a cathode material for solid oxide cells (SOCs), and has excellent performance. Not only can it achieve high current density in the solid oxide fuel cell (SOFC) mode; as a cathode material in the solid oxide electrolyzer (SOEC) mode, it also exhibits excellent efficiency in the co-electrolysis of CO2 and H2O.
[0036] The preparation method of the cerium oxide-based material of the present invention only requires simple heating and stirring to synthesize the powder, and does not require high temperature and high pressure operation or synthesis in an anhydrous and oxygen-free environment, which is convenient and fast and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Example 1 at a magnification of 50K;
[0038] Figure 2 The XRD spectrum of the cerium oxide-based material obtained in Example 1;
[0039] Figure 3 The current-voltage curve of the cerium oxide-based material obtained in Example 1 as an anode material in a solid oxide fuel cell (SOFC) mode;
[0040] Figure 4The current-voltage curve of the cerium oxide-based material obtained in Example 1 as a cathode material in a solid oxide electrolytic cell (SOEC) mode;
[0041] Figure 5 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Example 1 at a magnification of 5K;
[0042] Figure 6 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Example 2 at a magnification of 50K;
[0043] Figure 7 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Example 3 at a magnification of 50K;
[0044] Figure 8 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Example 4 at a magnification of 50K;
[0045] Fig. 9 This is a scanning electron microscope photo of a commercially available cerium oxide-based powder material at a magnification of 2.5K;
[0046] Fig.10 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Comparative Example 1 at a magnification of 20K;
[0047] Fig.11 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Comparative Example 2 at a magnification of 9.11K. DETAILED DESCRIPTION
[0048] The present invention is further described below by way of examples, but the present invention is not limited to these specific embodiments.
[0049] Example 1
[0050] The chemical formula of the cerium oxide-based material prepared in Example 1 is NiO / Ce 0.9 G 0.1 O 1.95 .
[0051] The cerium oxide-based material of Example 1 is obtained by a preparation method comprising the following steps:
[0052] Step 1): 1,3,5-benzenetricarboxylic acid is dissolved in an ethanol-deionized water solution;
[0053] In a specific embodiment of the present application, in step 1), the ethanol-deionized water solution is a solution obtained by mixing ethanol and deionized water in a volume ratio of 1:0.8 to 0.8:1. Preferably, specifically in this embodiment, ethanol and deionized water are mixed in a volume ratio of 1:1.
[0054] In a specific embodiment of the present application, in step 1), 1,3,5-benzenetricarboxylic acid is dissolved in an ethanol-deionized water solution, and the molar percentage of 1,3,5-benzenetricarboxylic acid after mixing is 0.3 to 0.8 mol / L. Preferably, specifically in this embodiment, the molar percentage of 1,3,5-benzenetricarboxylic acid is 0.5 mol / L.
[0055] Step 2): Mix a cerium metal salt and a rare earth metal salt in a first molar ratio and dissolve them in deionized water.
[0056] In one specific embodiment of the present application, the cerium metal salt is CeCl3, and the rare earth metal salt has the general formula of MCl3. In another specific embodiment of the present application, the cerium metal salt is Ce(NO3)3·6H2O; the rare earth metal salt has the general formula of M(NO3)3·6H2O.
[0057] In a specific embodiment of the present application, the M element in the general formula of the rare earth metal salt represents a metal element La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc or Y.
[0058] Preferably, in this embodiment, the M element is Gd. Preferably, in this embodiment, the cerium metal salt is Ce(NO3)3·6H2O, and the rare earth metal salt is Gd(NO3)3·6H2O.
[0059] In a specific embodiment of the present application, the first molar ratio is the molar ratio of Ce element to rare earth metal M element (a:b), wherein the value of a is 0.5-0.9, the value of b is 0.1-0.5, and the sum of a and b is 1.
[0060] Preferably, in this embodiment, the first molar ratio is 9:1 (the value of a is 0.9, and the value of b is 0.1).
[0061] Step 3): Mix the solutions obtained in step 1) and step 2), heat to 50-100° C., and stir continuously until the precipitate no longer increases; wash and dry the precipitate obtained by centrifugation to obtain a rare earth metal-doped Ce-MOF material.
[0062] In a specific embodiment of the present application, in step 3), the solutions obtained in step 1) and step 2) are mixed, and the total metal ion concentration of Ce element and M element after mixing is 0.07-0.13 mol / L.
[0063] Preferably, in this embodiment, in step 3), the solutions obtained in step 1) and step 2) are mixed, and the total metal ion concentration of Ce element and M element after mixing is 0.1 mol / L.
[0064] Specifically, 20 ml of the 1,3,5-benzenetricarboxylic acid solution (0.5 mol / L) obtained in step 1) was mixed with 80 ml of the solution (the molar concentration of the Ce element was 0.1125 mol / L, and the molar concentration of the Gd element was 0.0125 mol / L) obtained in step 2), and after mixing, the total metal ion concentration of the Ce element and the M element was 0.1 mol / L (wherein, the molar concentration of the Ce element was 0.09 mol / L, and the molar concentration of the Gd element was 0.01 mol / L).
[0065] In a specific embodiment of the present application, in step 3), the heating temperature is 50-100°C, and the heating and continuous stirring time is about 1-5 hours; specifically in this embodiment, the heating temperature is 60°C, the heating and continuous stirring is about 1-2 hours, and the precipitate hardly increases.
[0066] Specifically in this embodiment, in step 3), the precipitate obtained by centrifugation is washed three times with deionized water and anhydrous ethanol respectively, and the washed solid is dried in a vacuum oven at about 70° C. to finally obtain 2.3 g (0.013 mol) of rare earth metal-doped Ce-MOF material.
[0067] Step 4): dissolving Ni(NO3)2·6H2O and the rare earth metal-doped Ce-MOF material obtained above in an ethanol-deionized water solution according to a second molar ratio, heating to 50-100° C., and continuously stirring until the precipitate no longer increases; washing and drying the precipitate obtained by centrifugation;
[0068] In a specific embodiment of the present application, the second molar ratio is 1:2 to 3:1. Specifically in this embodiment, the second molar ratio is 1:1 (NiO loading ratio), 0.003 mol Ni(NO3)2·6H2O and 0.003 mol rare earth metal doped Ce-MOF material are mixed and dissolved in ethanol-deionized water solution.
[0069] In a specific embodiment of the present application, in step 4), the heating temperature is 50-100°C, and the heating and continuous stirring time is about 24-36 hours. Specifically in this embodiment, the heating temperature is 60°C, the heating and continuous stirring is about 24 hours, and the precipitate hardly increases.
[0070] In a specific embodiment of the present application, in step 4), the precipitate obtained by centrifugation is washed three times with deionized water and anhydrous ethanol respectively, and the washed solid is dried in a vacuum oven at about 70°C.
[0071] Step 5): The dried powder obtained in step 4) is calcined at a temperature of 500-900° C. to remove organic matter, thereby obtaining the cerium oxide-based material.
[0072] In this embodiment, in the step 5), the calcination temperature is 850° C. Specifically, the dried powder obtained in the step 4) is placed in a muffle furnace and calcined to obtain a sintered product.
[0073] Embodiment 2-4
[0074] The preparation method of the cerium oxide-based material of Examples 2-4 is different from the method of Example 1 only in that the second molar ratio is different; the contents of other steps are the same and will not be described in detail.
[0075] In the preparation method of Example 2, the second molar ratio is 3:1, and the obtained cerium oxide-based material NiO / Ce 0.9 G 0.1 O 1.95 In the a M b O 1.95 The mixing molar ratio of ” is 3:1.
[0076] In the preparation method of Example 3, the second molar ratio is 2:1, and the obtained cerium oxide-based material NiO / Ce 0.9 G 0.1 O 1.95 In the a M b O 1.95 The mixing molar ratio of ” is 2:1.
[0077] In the preparation method of Example 4, the second molar ratio is 1:2, and the obtained cerium oxide-based material NiO / Ce 0.9 G 0.1 O 1.95 In the a M b O 1.95 The mixing molar ratio of ” is 1:2.
[0078] Example 5-13
[0079] The cerium oxide-based materials of Examples 5-13 are:
[0080] NiO / Ce 0.9 La 0.1 O 1.95 、NiO / Ce 0.9 Pr 0.1 O 1.95 、NiO / Ce 0.9 Nd 0.1O 1.95 、NiO / Ce 0.9 Sm 0.1 O 1.95 、NiO / Ce 0.9 Eu 0.1 O 1.95 、NiO / Ce 0.9 Tb 0.1 O 1.95 、NiO / Ce 0.9 Dy 0.1 O 1.95 .
[0081] The preparation methods of Examples 5-13 differ from those of Example 1 only in that the rare earth metal salts used in step 2) are different; the contents of the other steps are the same and will not be described in detail.
[0082] The rare earth metal salts used in the preparation methods of Examples 5-13 are: La(NO3)3·6H2O, Pr(NO3)3·6H2O, Nd(NO3)3·6H2O, Sm(NO3)3·6H2O, Eu(NO3)3·6H2O, Tb(NO3)3·6H2O, and Dy(NO3)3·6H2O.
[0083] Comparative Example 1
[0084] The difference between Comparative Example 1 and Example 2 is that Comparative Example 1 is synthesized by a homogeneous precipitation method, which uses nickel nitrate, cerium nitrate, and gadolinium nitrate as raw materials and urea as a precipitant, including precipitation, separation, drying, and roasting.
[0085] Comparative Example 2
[0086] The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 is synthesized by a homogeneous precipitation method, which uses nickel nitrate, cerium nitrate, and gadolinium nitrate as raw materials and ammonia water as a precipitant, including precipitation, separation, drying, and roasting.
[0087] Commercially available products
[0088] The NiO / CGO type cerium oxide-based powder material purchased from Fuelcell Materials has the molecular formula NiO / Ce 0.9 G 0.1 O 1.95 , which is consistent with the embodiment.
[0089] Application Examples
[0090] The materials of Examples 1-13 can be used to make anode and cathode materials, and can also be used to make electrolyte materials.
[0091] Anode material
[0092] The preparation method of the anode material is to mix the cerium oxide-based powder material obtained in Example 1-13 with an organic additive (α-terpineol and ethyl cellulose) at a mass ratio of 1:1.5 to form a slurry, fully grind it on a three-roll grinder for about 2 hours, control the particle size to be about 10 μm, and remove excess air bubbles from the slurry with a vacuum defoamer to obtain an anode slurry. The anode slurry is coated on the electrolyte sheet in three layers, and then calcined at 1100° C. for 2 hours in air to form a half-cell.
[0093] Cathode material
[0094] The preparation method of the cathode material is to mix the cerium oxide-based powder material obtained in Example 1-13 with an organic additive (α-terpineol and ethyl cellulose) at a mass ratio of 1:1.5 to form a slurry, fully grind it on a three-roll grinder for about 2 hours, control the particle size to be about 10 μm, and remove excess air bubbles from the slurry with a vacuum defoamer to obtain a cathode slurry. The cathode slurry is coated on the electrolyte sheet in three layers, and then calcined at 1300° C. for 2 hours in air to form a half-cell.
[0095] Electrolyte materials
[0096] The preparation method of the electrolyte material is to mix the cerium oxide-based powder material obtained in Example 1-13 with ethanol, and the mixed powder is ball-milled on a roller mill for 24 hours to mix the ceramic particles evenly. The evenly mixed slurry is placed on a magnetic stirrer and dried while stirring at 120°C to make the dried powder particles evenly distributed. The dried slurry is ground using a grinding mortar to form a fine powder, and PVA is added as a binder during the grinding process. Then, the electrolyte plate is prepared by a tablet press, and 1g of powder is weighed each time during dry pressing to ensure that the size and thickness of the prepared green body are the same, and finally calcined at 1300°C in air for 2h.
[0097] Performance data
[0098] 1. Scanning Electron Microscope (SEM)
[0099] A Sigma 300 scanning electron microscope was used for testing, with an accelerating voltage of 2 kV and magnifications of 50K and 5K to capture the morphology and structure.
[0100] The scanning electron microscope photos of the cerium oxide-based material obtained in Example 1 at 50K and 5K magnifications are shown in FIG. Figure 1 and Figure 5 , from the figure we can see the one-dimensional rod bundle structure.
[0101] Figures 6 to 8 The following are scanning electron microscope photographs of the cerium oxide-based materials obtained in Examples 2 to 4 at a magnification of 50K.
[0102] From these figures, it can be seen that in the rod-like structure, the thin one-dimensional rod is GDC (Ce 0.9 G 0.1 O 1.95 ) rods, NiO particles are gathered on the rod surface and are highly dispersed. A complete rod is composed of many GDC rods and densely packed NiO particles on the rod surface.
[0103] The aspect ratio data of the materials were statistically analyzed using the obtained scanning electron microscope photos and ImageJ software.
[0104] The aspect ratio parameters of the cerium oxide-based material:
[0105] The aspect ratio of the cerium oxide-based material obtained in Example 1 is approximately in the range of 7.2-9.6, and its diameter is 0.42-0.54 μm (length is approximately 3.89-4.05 μm);
[0106] The aspect ratio of the cerium oxide-based material obtained in Example 2 is approximately in the range of 4.3-5.8, and its diameter is 0.61-0.73 μm (length is approximately 3.12-3.53 μm);
[0107] The aspect ratio of the cerium oxide-based material obtained in Example 3 is approximately in the range of 5.8-7.2, and its diameter is 0.54-0.61 μm (length is approximately 3.53-3.89 μm);
[0108] The aspect ratio of the cerium oxide-based material obtained in Example 4 is approximately in the range of 9.6-12.1, and its diameter is 0.37-0.42 μm (length is approximately 4.05-4.48 μm).
[0109] The aspect ratio results are shown in Table 1 below:
[0110] Table 1
[0111]
[0112]
[0113] Fig. 9 This is a scanning electron microscope photograph of a commercially available cerium oxide-based powder material at a magnification of 2.5K.
[0114] Fig.10 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Comparative Example 1 at a magnification of 20K. Fig.11 This is a scanning electron microscope photograph of the cerium oxide-based material obtained in Comparative Example 2 at a magnification of 9.11 K. As can be seen from the figure, both Comparative Examples 1 and 2 are nanoparticle structure materials, and do not have the one-dimensional rod bundle structure of Example 2 of the present application.
[0115] 2. XRD diffraction
[0116] The sintered product (rod bundle cerium oxide-based material) obtained in Example 1-13 was placed in a carrier as a cathode material. The X-ray diffractometer (ARL Equinox 3500) was set to a scanning angle of 10 to 80 degrees and a scanning time of 5 minutes to obtain its XRD spectrum. The data processing software Jade 6.0 was used to smooth the data, subtract the background, search for peaks, retrieve phases, mark characteristic peaks, read characteristic peak information, and compare the peak position with the standard card. The peak that meets a certain standard card contains the corresponding substance.
[0117] The XRD spectrum of the product of Example 1 is shown in Figure 2 ; Example XRD peak positions and "NiO" and "Ce 0.9 G 0.1 O 1.95 " completely corresponds to the standard card, proving that the sintered product obtained in Example 1 is NiO / Ce 0.9 G 0.1 O 1.95 .
[0118] 3. Electrochemical performance test
[0119] The entire electrochemical test is sealed with both positive and negative electrodes, the anode is in the air atmosphere, and the cathode is in the test atmosphere. The main structure of the battery test fixture is composed of an alumina ceramic tube, which is placed in a tubular heating furnace. The battery is sealed between two ceramic tubes with high-temperature ceramic sealant, and the two different electrodes of the battery are sealed to form two independent cavities to prevent gas leakage and cross-flow during the test. Platinum mesh is used for current collection on both electrode sides, and a layer of silver paste will be coated as the current collecting layer of the electrode before the test. The tubular heating furnace is heated at a heating rate of 10℃ / min to the operating temperature of 700-850℃ set for the battery test. The fuel gas and air are supplied to the two Al2O3 tubes respectively. Water vapor is injected into the evaporation chamber through a jet pump to control the flow rate, and then evaporates and mixes with other gases into the fuel chamber. The total gas flow rate into the fuel electrode and oxygen electrode is set to 20sccm. The electrochemical test was carried out using the German Zahner XC electrochemical workstation.
[0120] The electrochemical test results are shown in Table 2 below:
[0121] Table 2
[0122]
[0123] From Table 2 and Figure 3 , Figure 4The results show that in the solid oxide fuel cell (SOFC) mode, the cerium oxide-based material of Example 2 as the anode material can achieve up to 1.28 A / cm at 0.4 V in H2 atmosphere. 2 Current density; as a cathode material in solid oxide electrolysis cell (SOEC) mode, it also shows excellent efficiency in CO2 and H2O co-electrolysis, for example, 1.41A / cm at high temperature 850℃ and 1.5V 2 The current density is stable for up to 24 hours.
[0124] The electrochemical test results of Example 2, commercially available products, and Comparative Examples 1 and 2 are shown in Table 3 below:
[0125] Table 3
[0126]
[0127]
[0128] As can be seen from Table 3, Example 2 with a one-dimensional rod bundle structure has much higher performance than the commercially available product with only a nanoparticle structure, Comparative Example 1 and Comparative Example 2. Example 2 achieves 1.41 A / cm at a high temperature of 850°C and 1.5 V. 2 The current density is not only seven times higher than that of the nanoparticle-structured NiO-CGO cathode, but also has a stable current density for up to 24 hours. The cathode with a one-dimensional rod bundle structure is more than three times higher than the currently commercially available NiO-CGO when tested under the same operating conditions. Therefore, the development of a one-dimensional rod bundle structure improves the efficiency and durability of cathodes used for the co-electrolysis of CO2 and H2O.
[0129] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0130] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A cerium oxide-based material, characterized in that: The cerium oxide-based material has NiO / Ce a M b O 1.95 The general formula of In the general formula of the cerium oxide-based material, the M element represents a metal element La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc or Y; The value of a is 0.5~0.9, the value of b is 0.1~0.5, and the sum of a and b is 1; In the general formula of the cerium oxide-based material, "NiO" and "Ce a M b O 1.95 "The molar ratio is x:y, and the value of x:y is 1:2~3:1; The cerium oxide-based material has a one-dimensional rod bundle structure at the micrometer level; The cerium oxide-based material is obtained by a preparation method comprising the following steps; Step 1): 1,3,5-benzenetricarboxylic acid is dissolved in an ethanol-deionized water solution; Step 2): Mixing a cerium metal salt and a rare earth metal salt in a first molar ratio and dissolving them in deionized water; The cerium metal salt is CeCl3, and the rare earth metal salt has the general formula of MCl3; or, The cerium metal salt is Ce(NO3)3·6H2O, and the rare earth metal salt has a general formula of M(NO3)3·6H2O; Furthermore, the M element in the general formula of the rare earth metal salt is the M element in the general formula of the cerium oxide-based material; The first molar ratio is the ratio of a to b; Step 3): Mix the solutions obtained in step 1) and step 2), heat to 50-100° C., and stir continuously until the precipitate no longer increases; wash and dry the precipitate obtained by centrifugation to obtain a rare earth metal-doped Ce-MOF material; Step 4): Dissolve Ni(NO3)2·6H2O and the rare earth metal-doped Ce-MOF material in an ethanol-deionized water solution at a second molar ratio, heat to 50-100°C, and stir continuously until the precipitate no longer increases; wash and dry the precipitate obtained by centrifugation; The second molar ratio is the value of x:y; Step 5): The dried powder obtained in step 4) is calcined at a temperature of 500-900° C. to remove organic matter, thereby obtaining the cerium oxide-based material.
2. The cerium oxide-based material according to claim 1, characterized in that: In step 1) and step 4), the ethanol-deionized water solution is a solution obtained by mixing ethanol and deionized water in a volume ratio of 1:0.8 to 0.8:
1.
3. The cerium oxide-based material according to claim 2, characterized in that: In step 1) and step 4), the ethanol-deionized water solution is a solution in which ethanol and deionized water are mixed in a volume ratio of 1:
1.
4. The cerium oxide-based material according to claim 1, characterized in that: In step 1), 1,3,5-benzenetricarboxylic acid is dissolved in the ethanol-deionized water solution, and the molar percentage after mixing is 0.3-0.8 mol / L.
5. The cerium oxide-based material according to claim 1, characterized in that: In step 3), the solutions obtained in step 1) and step 2) are mixed, and the total metal ion concentration of Ce element and M element after mixing is 0.07-0.13 mol / L.
6. The cerium oxide-based material according to any one of claims 1 to 5, characterized in that: In the general formula of the cerium oxide-based material, M represents metal Gd.
7. The cerium oxide-based material according to claim 6, characterized in that: The first molar ratio is 9:1; the second molar ratio is 3:1, 2:1, 1:1 or 1:
2.
8. The cerium oxide-based material according to claim 6, characterized in that: The aspect ratio of the cerium oxide-based material is 4:1-12.5:1, and its diameter is 0.37-0.73 μm.
9. The cerium oxide-based material according to claim 8, characterized in that: The aspect ratio of the cerium oxide-based material is 4.3-5.8, and its diameter is 0.61-0.73 μm; or, The aspect ratio of the cerium oxide-based material is 5.8-7.2, and its diameter is 0.54-0.61 μm; or, The aspect ratio of the cerium oxide-based material is 7.2-9.6, and its diameter is 0.42-0.54 μm; or, The aspect ratio of the cerium oxide-based material is 9.6-12.1, and its diameter is 0.37-0.42 μm.
10. The cerium oxide-based material according to claim 6, characterized in that: In the step 3), the heating temperature is 60°C; in the step 3), the drying temperature is 70°C; in the step 4), the heating temperature is 60°C; in the step 4), the drying temperature is 70°C.
11. The cerium oxide-based material according to claim 10, characterized in that: In the step 5), the calcination temperature is 850°C.
12. The cerium oxide-based material according to claim 11, characterized in that: The dried powder obtained in step 4) is placed in a muffle furnace and calcined.
13. An electrode material, characterized in that: The electrode material comprises the cerium oxide-based material according to any one of claims 1 to 12; the electrode material is an anode material or a cathode material.
14. A fuel cell, characterized in that: The fuel cell uses the electrode material as claimed in claim 13.
15. An electrolytic cell, characterized in that: The electrolytic cell uses the electrode material as claimed in claim 14.
Citation Information
Patent Citations
Manufacturing of electrolyte-separation-membrane-free fuel cell by using cobalt-nickel-lithium oxide and cerium oxide-doped composite material
CN104882623A
Manufacturing of low-temperature solid oxide fuel cell with cobalt-nickel- aluminum-lithium oxide and doped cerium oxide composite material
CN105006580A